Analisis Implementasi Keselamatan Dan Kesehatan Kerja (K3) Sebagai Upaya Pencegahan Kecelakaan Kerja Pada Karyawan PT. PLN (Persero) Unit Layanan Transmisi Dan Gardu Induk (ULTG) Kendari - Lisa Febyola; Asnia Zainuddin; Febriana Muchtar (KOLONI, 2025)
Human Resource Management (HRM) is an important role for the success of an organization or company, because people are living assets that need to be maintained and developed. One of the things that must be the main concern for human resource managers is occupational health and safety (K3). Occupational safety and health (K3) is an effort to prevent the possibility of work accidents and diseases caused by work and the work environment. Objective: to find out an overview of the implementation of K3 as an effort to prevent work accidents among employees at PT PLN (Persero) ULTG Kendari. Method: The research method used in this research is a qualitative research method, with data collection techniques through interviews, observation and documentation. The research results concluded that K3 implementation had been implemented. PT PLN ULTG Kendari is advised to increase education and socialization on the use of APD to increase workers' awareness of using APD while carrying out work.